On a novel co-rotating synchronous turbine mode operation in a centrifugal compressor - Rajendran, David John; Anselmi Palma, Eduardo; Roumeliotis, Ioannis; Pachidis, Vassilios; Sayre, David; Howarth, Nicholas (American Society of Mechanical Engineers (ASME), 2026)
A novel co-rotating, synchronous, reverse flow (RF) turbine mode operation in a centrifugal compressor (CC) is investigated, and methods to enable this mode, its working principles, flow field features, and key performance characteristics are described. This is done by using three-dimensional (3D) Reynolds–averaged Navier–Stokes (RANS) flow field simulations on a simplified variant of the NASA High Efficiency Centrifugal Compressor (HECC) geometry, which represents a typical state-of-the-art design practice. The novel co-rotating turbine mode is elucidated by first considering the baseline contra-rotating, reverse flow turbine mode as would be expected from the conventional four-quadrant CC operation map. This baseline contra-rotating turbine mode is also hitherto undescribed in the literature for CC. Therefore, the flow field and performance metrics in the baseline contra-rotating mode are utilized to provide insights into the possibility of engineering design elements that can enable the novel co-rotating turbine mode. The novel co-rotating, turbine mode is found to be enabled by the introduction of a suitable swirl generation mechanism that will direct the flow onto the impeller wheel suction side to give it a rotational impulse to spin from the suction to the pressure side as in nominal operation. The flow expansion through the reversed impeller wheel flow path with radius reduction enables power production. In the novel co-rotating, turbine mode, the flow leaves the impeller wheel in the same direction as it enters because of the direction of rotation and impeller inlet flow angle. However, this does not significantly impact power production because of the reduced radius weighting of the absolute swirl at the impeller inlet. An exemplary co-rotating turbine mode enabling configuration with 45 deg rotated diffuser vanes is found to handle up to 46% higher reverse flow and yield 6.25% higher peak power output even with a 16% lower absolute swirl velocity change as compared to the baseline contra-rotating mode. Additionally, the novel mode indicates better low speed power profile and wheel terminal speed as well. Alternative embodiments to enable the co-rotating mode like drilled feed ports and guide vane arrangements are discussed in the work. The hitherto undescribed co-rotating turbine mode operation is unique in its ability to produce and absorb power in the same shaft for bladed turbomachinery. Therefore, purposeful utilization of this mode could enable the design of better, robust, optimized systems for aerospace and energy applications.
See also: https://doi.org/10.1115/1.4070125 Copyright © 2025 by Rolls-Royce plc
Keywords: 40 Engineering; 7 Affordable and Clean Energy; Energy; 4001 Aerospace engineering; 4004 Chemical engineering; reverse flow; turbine mode; power production; centrifugal compressor; system design